2020
DOI: 10.3390/molecules25194554
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resveratrol in Mammalian Reproduction

Abstract: Resveratrol is one of the most investigated natural polyphenolic compounds and is contained in more than 70 types of plants and in red wine. The widespread interest in this polyphenol derives from its antioxidant, anti-inflammatory and anti-aging properties. Several studies have established that resveratrol regulates animal reproduction. However, the mechanisms of action and the potential therapeutic effects are still unclear. This review aims to clarify the role of resveratrol in male and female reproductive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 143 publications
0
84
0
Order By: Relevance
“…Our data reveal some similarities between the effects observed after NRG and RESV treatment. Some studies reported that RESV acts as a regulator of male reproductive function [ 78 , 79 ] and it has been suggested that RESV arguably improves semen quality in humans [ 80 ] when this molecule is added to a cryopreservation medium.…”
Section: Discussionmentioning
confidence: 99%
“…Our data reveal some similarities between the effects observed after NRG and RESV treatment. Some studies reported that RESV acts as a regulator of male reproductive function [ 78 , 79 ] and it has been suggested that RESV arguably improves semen quality in humans [ 80 ] when this molecule is added to a cryopreservation medium.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasing trends toward delaying childbearing, there is a growing interest in establishing prophylactic and therapeutic strategies to counteract age-related reproductive failure. RES has been indicated as an anti-aging dietetic supplement with potential beneficial effects on age-related reproductive decline [ 21 , 22 ]. The present study shows that female mice supplemented with RES over 10 consecutive weeks displayed slightly better reproductive performances compared to not-supplemented sibling controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have investigated the beneficial effects of RSV on experimental animals, there are few clinical trials in humans on the relationship between this compound and male fertility and the results are often controversial [ 10 ]. A recent review evaluated the impact of RSV on male and female reproduction, by analyzing studies both on human and animal models [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have investigated the beneficial effects of RSV on experimental animals, there are few clinical trials in humans on the relationship between this compound and male fertility and the results are often controversial [ 10 ]. A recent review evaluated the impact of RSV on male and female reproduction, by analyzing studies both on human and animal models [ 10 ]. The authors concluded that, although a considerable amount of research supports the positive impact of RSV on human and animal reproduction, further studies are necessary to consolidate the knowledge on the properties of RSV and its role in reproductive functions.…”
Section: Introductionmentioning
confidence: 99%